Probability based design of punching shear resistance of column to slab connections - Vainiūnas, Povilas; Šalna, Remigijus; Šakinis, Dainius (Journal of Civil Engineering and Management, 2015)
The paper analyzes the dependence of punching shear strength reliability index β, calculated according to EN 1992-1-1:2004 (2004) and STR 2.05.05:2005 (2005) in reinforced concrete floor slab-to-column joint on the values of random factors. The paper deals with theoretical research of the influence of independent random variables, such us the value of the characteristic compressive strength fck of concrete, the area As of the longitudinal reinforcement, effective cross-section depth d and the ratio of the self-weight and the effective load on the value of the reliability index β. The paper presents experimental results of reinforced concrete slabs with different longitudinal reinforcement ratio ρ subjected to a concentrated load. I t was determined that when the effective load makes around 50% of the construction self-weight load, i.e. Gk /Qk = 2 and when minimal variation coefficient estimates are taken (for concrete strength δfc = 0.1, for effective depth δd = 0,1 and for the area of longitudinal reinforcement cross-section δAs = 0.05 or δAs = 0.075 and when Gk = Qk i.e. Gk /Qk = 1 where δfc = 0.1, δd = 0.1 and δAs = 0.05) the reliability index β of the analyzed slabs calculated according to EN 1992-1-1:2004 (2004) as well as β calculated according to STR 2.05.05:2005 (2005), is bigger than EN 1990:2002 (2002) recommendation for the minimum value of reliability index – 3.8 for RC2 construction reliability class ultimate. In other cases the reliability index β is close to 3.8 or much smaller than 3.8.